2013
DOI: 10.1007/s10995-012-1217-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental Immigration Status is Associated with Children’s Health Care Utilization: Findings from the 2003 New Immigrant Survey of US Legal Permanent Residents

Abstract: Our objective was to examine the association between parental immigration status and child health and health care utilization. Using data from a national sample of immigrant adults who had recently become legal permanent residents (LPR), children (n = 2,170) were categorized according to their parents’ immigration status prior to LPR: legalized, mixed-status, refugee, temporary resident, or undocumented. Logistic regression with generalized estimating equations was used to compare child health and health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Furthermore, beyond shared cultural understanding, other individual characteristics, such as poverty and traumatic experiences, were also identified as factors influencing health literacy. These findings are consistent with existing research that have demonstrated the influence of socioeconomic status and other demographic factors on health literacy (Yun et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, beyond shared cultural understanding, other individual characteristics, such as poverty and traumatic experiences, were also identified as factors influencing health literacy. These findings are consistent with existing research that have demonstrated the influence of socioeconomic status and other demographic factors on health literacy (Yun et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The survey assessed parent report of provider-diagnosed conditions and may underestimate the prevalence of health conditions in children with less healthcare access. Parent-reported health conditions may be over-reported or under-reported due to the parent’s education level and ethnicity (59), English language proficiency (9, 60) and legal status (7, 32, 61, 62). Study strengths include the large study population, racial/ethnic diversity of the children, the administration of the survey in five languages, and inclusion of less prevalent health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, differential healthcare access and health outcomes have been found for children from immigrant families. Studies have shown that immigrant children and native-born children of immigrant parents are more likely to lack health insurance and access to healthcare than native-born children of native-born parents [36]. There is also evidence that immigrant parents are less aware of health and community resources than native-born parents [7], and that children of immigrant parents are more likely to report poor physical health than children of native-born parents [8].…”
Section: Introductionmentioning
confidence: 99%